Determining the Illegal Waste Disposal in Coastal Area using Transect Walk Approach - Badrus Zaman; Anik Sarminingsih; Ika Bagus Priyambada; Mochamad Arief Budihardjo; Bimastyaji Surya Ramadan; Uus Uswatun Hasanah (Journal of Governance Risk Management Compliance and Sustainability, 2023)
The increasing population and anthropogenic activities in cities/regencies in Indonesia have caused many waste-related problems, which can trigger environmental and human health. In addition to population growth, rapid economic development has resulted in an increasing amount and type of waste. The coastal area is one area that still needs to get adequate solid waste services. There have been many studies on waste management. However, research has yet to examine the amount and composition of waste generation in coastal areas that have not been served by waste management.. This study shows the waste generation and composition trend in coastal areas that must be served in waste management and determines the appropriate waste management strategy. This research method uses a transect walk survey carried out by following a predetermined route in the area. Paths are made randomly by forming circles or straight lines for 10 km. The composition of illegal waste dumps found included leaves (69.02%), plastic (15.24%), branches and twigs (9.93%), paper and cardboard (3.75%), food waste (1.97%), and rubber (0.1%). At least 1.59 tonnes/day of illegal waste is estimated in Sidorejo Village. While this figure increases at the district level, the amount of unaccommodated waste is estimated at 19.85 tonnes/day. Efforts to handle waste that can be done are changing the mindset and paradigm of the community through an educational approach, improving the waste management system by providing waste facilities and reducing the amount of waste collected through a simple program (Reuses, Reduces, Recycle) that involves the community.